2019
DOI: 10.3389/fpsyg.2019.01127
|View full text |Cite
|
Sign up to set email alerts
|

Is tDCS an Adjunct Ergogenic Resource for Improving Muscular Strength and Endurance Performance? A Systematic Review

Abstract: Exercise performance is influenced by many physical factors, such as muscle strength and endurance. Particularly in the physical fitness and sports performance contexts, there are many types of ergogenic aids to improve muscular strength and endurance performance, with non-athletes and even athletes using illegal drugs to reach the top. Thus, the development of innovative methods to aid in exercise performance is of great interest. One such method is transcranial direct current stimulation (tDCS). A systematic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 71 publications
(337 reference statements)
4
36
0
1
Order By: Relevance
“…The small effects we 297 report here are also similar to the standardized effects reported by Radel et al, (2017). The results 298 of these two pre-registered studies, plus other exploratory studies (Kan et al, 2013;Flood et al, 299 2017) and recent systematic reviews (Holgado et al, 2019;Machado et al, 2019), suggest that, 300 contrary to recent proposals (Angius et al, 2017;Edward et al, 2017), tDCS does not enhance 301 exercise performance, at least not for a sustained isometric contraction. However, it should be 302 noted that in 13 of the 20 participants, at least one condition (1 or 2 mA) improved exercise time 303 compared to sham (data available: https://osf.io/rh82g/files).…”
Section: Procedures 128supporting
confidence: 73%
“…The small effects we 297 report here are also similar to the standardized effects reported by Radel et al, (2017). The results 298 of these two pre-registered studies, plus other exploratory studies (Kan et al, 2013;Flood et al, 299 2017) and recent systematic reviews (Holgado et al, 2019;Machado et al, 2019), suggest that, 300 contrary to recent proposals (Angius et al, 2017;Edward et al, 2017), tDCS does not enhance 301 exercise performance, at least not for a sustained isometric contraction. However, it should be 302 noted that in 13 of the 20 participants, at least one condition (1 or 2 mA) improved exercise time 303 compared to sham (data available: https://osf.io/rh82g/files).…”
Section: Procedures 128supporting
confidence: 73%
“…From this study, it is very obvious that most staff members came from the non-innovative curriculum with significant response 0.05, yet they make use of attending and participating in FDAP, which indicates its usefulness in providing chances for learning new skills, as proved by other studies [26][27][28]. The study observed that 84% of the faculty members are interested in the presentation, which is in agreement with other studies [29,30], while 86% consider it as enriching their experience as teaching staff, which add a lot of skills to them, in finding that it is confirmed by other authorities (31).…”
Section: Discussionsupporting
confidence: 57%
“…Fatigue is an important clinical outcome in tDCS studies and has been investigated in healthy subjects [21][22][23][24] and patients with neurological or psychiatric disorders [25][26][27][28]. However, tDCS studies on fatigue, especially in neurological disorders, have elicited conflicting results.…”
Section: Introductionmentioning
confidence: 99%